The radio advertising in Brazil: the phases of its historical evolution (1922-1990) - Reis, Clóvis (2022)
According to the results of studies about broadcasting media in Brazil, the history of the radio is divided in three phases. The first embraces the period between 1922 and 1935, that corresponds to the experimental transmission stage. The second period (1935-1955) is characterized by the consolidation of the radio as a media. The last one, the period between 1955 and 1976, reflects the lost of media space due to the television. The present paper has the main proposal to describe the development of the radio as a media in Brazil and its role as advertising in every period. This paper also explains the use of radio advertising after the 70's.